Comparative study on copper leaching from waste printed circuit boards by typical ionic liquid acids. (July 2015) - Chen, Mengjun; Huang, Jinxiu; Ogunseitan, Oladele A.; Zhu, Nengming; Wang, Yan-min
Abstract : Graphical abstract: Highlights: Ionic liquid (IL) was used to leach copper from WPCBs. Copper can be successfully leached out by the six IL acids, nearly 100%. IL acids show a similar behavior with common inorganic acids, except temperature. For IL acids, diffusion plays a more important role than surface reaction. Abstract: Waste printed circuit boards (WPCBs) are attracting increasing concerns because the recovery of its content of valuable metallic resources is hampered by the presence of hazardous substances. In this study, we used ionic liquids (IL) to leach copper from WPCBs. [BSO3 HPy]OTf, [BSO3 HMIm]OTf, [BSO4 HPy]HSO4, [BSO4 HMim]HSO4 and [MIm]HSO4 were selected. Factors that affect copper leaching rate were investigated in detail and their leaching kinetics were also examined with the comparison of [Bmim]HSO4 . The results showed that all six IL acids could successfully leach copper out, with near 100% recovery. WPCB particle size and leaching time had similar influences on copper leaching performance, while IL acid concentration, hydrogen peroxide addition, solid to liquid ratio, temperature, showed different influences. Moreover, IL acid with HSO4 − was more efficient than IL acid with CF3 SO3 − . These six IL acids indicate a similar behavior with common inorganic acids, except temperature since copper leaching rate of some IL acids decreases with its increase. The results of leaching kinetics studies showed that diffusion plays a more important role than surface reaction, whereas copper leaching by inorganic acids is usually controlled by surface reaction. This innovation provides a new option for recovering valuable materials such as copper from WPCBs.